Impact of Therapist Training on Parent Attendance in Mental Health Services for Children with ASD. Issue 2 (4th March 2022) - Dickson, Kelsey S.; Chlebowski, Colby; Haine-Schlagel, Rachel; Ganger, Bill; Brookman-Frazee, Lauren
ABSTRACT: Objective: The current study explored the impact of training therapists in a mental health intervention for children with autism spectrum disorder (ASD) on parent attendance in their children's therapy sessions. We also examined family, therapist, and program factors as potential moderators. Method: Data were drawn from a cluster-randomized community effectiveness trial of "An Individualized Mental Health Intervention for ASD (AIM HI)". Participants included 168 therapists yoked with 189 children recruited from publicly-funded mental health services. Data included family (caregiver strain, parent sense of competence, race/ethnicity), therapist (background, experience), and program (service setting) characteristics, and parent session attendance. Multilevel models were used to evaluate the effectiveness of AIM HI therapist training on caregiver attendance and identify moderators of training effects on parent attendance. Results: Parents attended a higher percentage of sessions in the AIM HI training condition compared to the Usual Care condition. Program service setting moderated the effect of AIM HI training, with higher parent attendance in non-school (mostly outpatient) settings compared to school settings and a significantly smaller difference between the settings in the AIM HI condition. Conclusions: Effective strategies to promote parent engagement, especially in service settings such as schools, are warranted. Findings support the effectiveness of AIM HI training in promoting parent attendance across multiple publicly-funded mental health service settings. The larger effect in school-based programs supports the utility of training in evidence-based interventions such as AIM HI to increase the feasibility of parent attendance in such services.